2009
DOI: 10.1016/j.febslet.2009.09.020
|View full text |Cite
|
Sign up to set email alerts
|

A distinct structural region of the prokaryotic ubiquitin‐like protein (Pup) is recognized by the N‐terminal domain of the proteasomal ATPase Mpa

Abstract: Edited by Miguel De la RosaKeywords: Prokaryotic ubiquitin-like protein Mpa ARC Proteasome NMR Mycobacterium tuberculosis a b s t r a c tThe mycobacterial ubiquitin-like protein Pup is coupled to proteins, thereby rendering them as substrates for proteasome-mediated degradation. The Pup-tagged proteins are recruited by the proteasomal ATPase Mpa (also called ARC). Using a combination of biochemical and NMR methods, we characterize the structural determinants of Pup and its interaction with Mpa, demonstrating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
119
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(128 citation statements)
references
References 32 publications
(66 reference statements)
7
119
0
Order By: Relevance
“…Both linear fusions in mycobacterium mutants and overproduction of Pup lacking its N-terminal region strongly support this hypothesis. We found that the C-terminal half of Pup, in addition to the proteasomal ATPase Mpa, is required to interact with pupylation enzymes (4,14,17,19). Taken together, we propose a model where (i) the C-terminal half of Pup interacts with enzymes to facilitate pupylation, (ii) the same region interacts with Mpa to target the protein to the proteasome, and (iii) the N-terminal half of Pup initiates degradation by the proteasome.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Both linear fusions in mycobacterium mutants and overproduction of Pup lacking its N-terminal region strongly support this hypothesis. We found that the C-terminal half of Pup, in addition to the proteasomal ATPase Mpa, is required to interact with pupylation enzymes (4,14,17,19). Taken together, we propose a model where (i) the C-terminal half of Pup interacts with enzymes to facilitate pupylation, (ii) the same region interacts with Mpa to target the protein to the proteasome, and (iii) the N-terminal half of Pup initiates degradation by the proteasome.…”
mentioning
confidence: 81%
“…NMR analysis determined that Mpa interacts with the Cterminal half of Pup but not with the disordered N terminus (4,14,19). In addition to providing an unstructured degron for proteasome substrates, we hypothesized that the N terminus of Pup interacts with enzymes of the pupylation pathway.…”
mentioning
confidence: 99%
“…his 6 6 i27-tev-cys-pup E ). Labeling with 5-iodoacetamidofluorescein was carried out following binding of the protein to the Ni 2ϩ -NTA column.…”
Section: Methodsmentioning
confidence: 99%
“…7) Proteasome accessory factor A then ligates Pup to target proteins by catalyzing the formation of an isopeptide bond between the C-terminal glutamate of Pup and the "-amino group of lysines in the substrates. In degrading pupylated proteins, the proteasomal ATPase complex (ARC) recruits pupylated proteins by binding Pup to its N-terminal coiled-coil domains, 8,9) and the substrates are then translocated through the ATPase pore into the proteasomal catalytic chamber. 10) In this Pup-dependent proteolytic system, Dop functions not only as a deaminase of Pup but also as a depupylase, removing Pup from pupylated substrates by cleaving the isopeptide bond between Pup and the target proteins.…”
mentioning
confidence: 99%